The Willingness to Pay Premium Luxurious Cosmetics Product based on Brand Equity mediated by Hedonic Value of Live Streaming Users - Saajida, Alya; Rufaidah, Popy (JURNAL MANAJEMEN MOTIVASI, 2026)
This study investigates how brand equity influences consumers' willingness to pay a premium for Yves Saint Laurent (YSL) cosmetics through the mediating role of hedonic value. Using a quantitative approach with purposive sampling, data were collected from 108 social media users who had viewed YSL’s live-streaming ads and analyzed via SEM-PLS. Results show brand equity positively affects both hedonic value and willingness to pay a premium. Hedonic value also significantly enhances willingness to pay more. Consumers’ readiness to pay higher prices for luxury cosmetics is shaped by brand strength and the pleasure derived from the products.